Agricultural Commodities’ Research Associated with Economic Activities in the Past 20 Years : A Bibliometric Analysis - Rani, Pallavi; Kumar, Sanjay (Indian Journal of Research in Capital Markets, 2023)
Background : Research has been conducted on agricultural commodities for many years. Studies on agri-commodities are numerous. While many academics link their studies to global commodities exchanges, many others concentrated on the unpredictable prices of agricultural commodities. A few scholars examined the connections among energy, oil, and agricultural products. Conversely, other scholars investigated the effectiveness and hazards of futures markets, global trade regulations, food securities, and so on. Purpose : This review analysis aimed to investigate the trends in the research domain of agri-commodities, which have been associated with economic activities in the past 20 years. Methodology : Bibliometric analysis helped us to identify those trends. We used the Web of Science core collection for the data collection and Vosviwer software for bibliographic data analysis. Findings : The research findings suggested that agricultural commodities can be a good research area for researchers associated with economics, commerce, and management, as agri-commodities have added many new dimensions to their domain in the past decades. Practical Implications : The study’s findings would benefit future researchers in finding the research gap in the Indian agricultural commodity derivatives market. They could discover the research areas they want to study about Indian agricultural commodities. Originality : We attest that this research paper’s intellectual substance is entirely our creation and that all sources and help used in its preparation have been appropriately cited.